Mobile vision-based rehabilitation system for upper limb exercises - Choo, Calvin Zhe Kai (Nanyang Technological University, 2021)
In a world where technology is advancing rapidly, every industry must keep up to new standards. The medical field has benefited from this rapid advancement in technology, and it has helped provide digital solutions to many healthcare problems. This project explores the design of an Android Mobile Device (smartphone or tablet)-Based System that uses the built-in camera to monitor and measure the incremental movement capabilities of stroke patients, as they use the system in a home setting.